1991
DOI: 10.1248/cpb.39.1018
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of heat sterilization of liposomes.

Abstract: Several kinds of liposomes were sterilized at 121 degrees C for 20 min. They tended to aggregate after heat sterilization (HS) in saline, while no aggregation was observed in an isotonized sugar or polyol solution. The dispersions containing egg phosphatidylcholine (EggPC) with a high peroxide value (POV) turned slightly yellowish after HS. This color change was prevented by using EggPC with a low POV, hydrogenated EggPC (H-EggPC) or dipalmitoylphosphatidylcholine (DPPC). Nitrogen gas bubbling at neutral pH al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 0 publications
3
33
0
Order By: Relevance
“…The fluorescence value is corrected for the increased fluorescence been noted by others as well (25). However, when intensity of free sulforhodamine B dye in methanol compared with placed in SHB, it was found that liposomes retain their SSC or SHB.…”
Section: Tures (121њc) In Osmotically Balanced Solutions Hasmentioning
confidence: 83%
“…The fluorescence value is corrected for the increased fluorescence been noted by others as well (25). However, when intensity of free sulforhodamine B dye in methanol compared with placed in SHB, it was found that liposomes retain their SSC or SHB.…”
Section: Tures (121њc) In Osmotically Balanced Solutions Hasmentioning
confidence: 83%
“…Leakage of encapsulated CF indicated that vesicles prepared from TPL containing higher amounts of caldarchaeol lipids generally had lower amounts of CF leakage. The potential benefit of caldarchaeol lipids in preventing leakage was confirmed by the observation that the leakage from M. mazei TPL vesicles (100%archaeols) was reduced after incorporation of progressively higher proportions of TPL from T. acidophilum, which contains about 90% caldarchaeols (Kikuchi et al, 1991). The stability of M. mazei archaeosomes could alternatively be improved by incorporation of cholesterol similar to that seen with ester liposomes.…”
Section: Thermal Stabilitymentioning
confidence: 87%
“…The maximum thermal stability (60 C) of vesicles made from S. solfataricus polar lipid fraction Pressurized liquid extraction (PLE) when mixed with egg Phosphatidylcholine (PC) was reported when the lipids were used at a molar ratio of 1:2, and these vesicles were more thermo-stable than those made from the PLE lipid alone (Gregoriadis, 1995). The stability of vesicles made from mixtures of TPL (consisting of natural mixtures of archaeol and caldarchaeol lipids) with egg PC demonstrated that the stability at 37 C was related to the greater content of the polar ether lipids in the mixture (Kikuchi et al, 1991). Comparative thermal stability of vesicles made from a highly purified caldarchaeol subfraction from TPL of S. acidocaldarius with those made from unsaturated palmitoyl-oleoyl phosphatidylcholine, or saturated diphytanoyl phosphatidylcholine, showed that unlike the latter two that become very permeable at 35-40 C, the caldarchaeol lipid vesicles were not sensitive to leakage up to 60 C, and at 80 C released55% of encapsulated CF marker dye.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…These systems include archaelipids naturally designed for such purposes (Fan et al, 1995;Khan and Chong, 2000) as well as suspensions of small vesicles made with phosphocholines and containing minimal dissolved oxygen (Kikuchi et al, 1991;Zuidam et al, 1993). In the latter reference, autoclaving was explored as a means of sterilizing submicron vesicles that were too large for filtration through 0.22 m filters.…”
Section: Thermal Stability Of Polymer Vesiclesmentioning
confidence: 99%